MENINGKATKAN HASIL BELAJAR IPA MELALUI METODE INQUIRY PADA SISWA KELAS V SD - Dewi, Melinda Puspita; Kristin, Firosalia (Mimbar Sekolah Dasar, 2017)
The aim of this research is to describe inquiry method steps on improving the science study result of 5th graders in SD Negeri 1 Bawen that is located in Bawen, Central Java. The students are in 2nd semester, academic year 2016/2017. The subjects of this research are 24 students who are 5th grader in SD Negeri 1 Bawen. This research is a class action research through two cycles. The study method used is inquiry method. The data collection techniques are both test and non test. Descriptive comparative analysis is used in analyzing the data. The result of this research shows that inquiry study method can improve the science study result of the 5th grader in SD Negeri 1 Bawen, from cognitive, affective, and psychomotor aspects. This is supported by data that have been analyzed, from the condition in the beginning, 1st cycle, and 2nd cycle. In conclusion, inquiry method can improve the science study result of 5th graders in SD Negeri 1 Bawen.Keywords: study result, science, inquiry method.